PENGARUH PENAMBAHAN BERBAGAI JENIS SUMBER KARBOHIDRAT PADA SILASE LIMBAH SAYURAN TERHADAP KUALITAS FISIK DAN TINGKAT PALATABILITAS SILASE - Alvianto, Angga; ,, Muhtarudin; ., Erwanto (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
Vegetable waste in the traditional market can be used as feed.Â  Nevertheless, the shortcomings from vegetable waste is have a high level of water content.Â  Vegetables waste can be processed to be silage with addition accelerators that is rice brain, cassava flour, molasses. The purpose of this study was to compare the effect of several sources of carbohydrate of the physical quality of silage and silage palatability level vegetable waste, knowing the source of carbohydrate that have the best effect on the physical quality and level of palatability of silage vegetable waste. This research is completely randomized design (CRD) with 4 treatment additional source of carbohydrates (rice bran, cassava flour, molasses and silage without the addition of accelerator) and 3 repetitions. Data was analyzed by Analysis of Varians and continued with Least Significant Difference Test (LSD) 0,01 or 0,05. The results showed the addition of various sources of carbohydrate significantly (P <0.05) on the texture and highly significant (P <0.01) on the color and flavour of vegetable waste silage. Treatment with the addition of cassava flour is the best treatment that affects texture and color silage, Whereas treatment with the addition of molasses is the best treatment that affects the flavour and palatability of silage. Keywords: silage, rice bran, cassava flour, molasse), physical quality and palatability of silage.